Multimodal ultrasonographic algorithm in the differentiation of submandibular masses. (3rd June 2017) - Knopf, Andreas; Cortolezis, Nikolaus; Bas, Murat; Mansour, Naglaa; Hofauer, Benedikt
Abstract: Conclusion: The multimodal diagnostic algorithm is a simple diagnostic tool in the pre-operative assessment of submandibular masses that enables one-stage surgical concepts. Background: The pre-operative assessment of submandibular masses is of major clinical impact. This study assesses the diagnostic utility of a newly introduced diagnostic algorithm in the differentiation of submandibular masses based on epidemiological and B-mode ultrasonographic data. Methods: One hundred and eighty-eight patients with submandibular triangle masses were included. Epidemiological and ultrasonographic data of 128 consecutively included patients were assessed and structured in a multimodal algorithm. The diagnostic algorithm was prospectively validated in a further 60 patients. Results: Single epidemiological and ultrasonographic data do not reliably predict the lesional entity. The multimodal diagnostic algorithm achieved a diagnostic sensitivity/specificity of 100%/100% in sialolithiasis, 44%/100% in benign submandibular gland diseases (BSD), 94%/96% in nodal lymphoma/unspecific lymphadenitis, and 91%/84% in carcinomas. Reduced sensitivity in BSD or specificity in carcinomas increased after intra-operative fresh frozen section in patients suspected for BSD.